2004
DOI: 10.1097/01.jom.0000144998.82543.9d
|View full text |Cite
|
Sign up to set email alerts
|

Do Subject Characteristics Modify the Effects of Particulate Air Pollution on Daily Mortality Among the Elderly?

Abstract: Our results provide insight into factors possibly conferring susceptibility to the acute effect of urban air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
5
20
0
Order By: Relevance
“…Assuming that the educational strata have some validity, it is possible that people who are less educated and who survive to older ages, despite infection, poor health care, inadequate nutrition, or other disadvantages throughout the life course, represent highly resilient "healthy survivors," whereas the more highly educated groups include individuals with a larger range of frailty, thus explaining the results seen in our cities and in France. 5,6 Although evidence suggests that the health of men and women can be patterned differently by educational status (eg, life expectancy reductions with diminishing years of schooling were even greater among Chilean men compared with women 38 ), and lower education modified air pollution risk only among women in Poland, 9 we did not see consistently different effects by sex in these Latin American cities.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Assuming that the educational strata have some validity, it is possible that people who are less educated and who survive to older ages, despite infection, poor health care, inadequate nutrition, or other disadvantages throughout the life course, represent highly resilient "healthy survivors," whereas the more highly educated groups include individuals with a larger range of frailty, thus explaining the results seen in our cities and in France. 5,6 Although evidence suggests that the health of men and women can be patterned differently by educational status (eg, life expectancy reductions with diminishing years of schooling were even greater among Chilean men compared with women 38 ), and lower education modified air pollution risk only among women in Poland, 9 we did not see consistently different effects by sex in these Latin American cities.…”
Section: Discussionmentioning
confidence: 51%
“…12 In French cities, however, both long-and short-term associations between particles and mortality showed higher associations among the more highly educated, when considering 3 educational attainment categories. 5,6 The heterogeneous patterns we observed by educational attainment may relate to the way education interacts with other aspects of the social context to affect health and underlying susceptibility. A survey of elderly adults in these cities examined equity of access to health care by socioeconomic indicators, including education.…”
Section: Discussionmentioning
confidence: 90%
“…Social factors in addition to physiology can affect the susceptibility as well (Makri and Stilianakis, 2008). Behaviors of the elderly can lead to exposure that differs from younger adults (Filleul et al, 2004). There is greater awareness among the elderly on heat (Kalkstein and Sheridan, 2007;Kim et al, 2014), and confinement to indoor environments on very hot days may decrease exposure to ambient air pollutants.…”
Section: Discussionmentioning
confidence: 98%
“…27 In their casecrossover study in Bordeaux (France), Filleul et al observed statistically significant associations only in subjects who were blue-collar workers, but found no statistically significant association when the study population was stratified according to educational level. 37 In a cohort study of the same population, which compared the characteristics of people who died on days when the highest and lowest black smoke concentrations were observed (that is, above the 90th and below the 10th percentile of observed concentrations), Filleul et al found that neither past occupational status nor educational level modified the effect of pollution on mortality. 43 Villeneuve et al found no modification by mean family income, assessed by enumeration area, of the effect of either total suspended particulates (TSP) or PM 2.5 .…”
Section: Mortality For Those 65 Years or Oldermentioning
confidence: 99%
“…26 28 36 The temporal resolution of exposure measurements (a day, 43 mean of several days 34 ) and delayed effects (lags) tested also differs slightly between studies. These studies use socioeconomic variables that are very diverse in both in their nature (eg, educational level, income, percentage of unemployed people in the neighbourhood, composite deprivation index) and their resolution (individuals, 37 cities, 36 districts, 40 author-defined city subdivisions, 26 32 enumeration areas, 34 and ZIP codes 33 ). Moreover, for the same type of socioeconomic variable, different studies sometimes use different cut-off points for defining deprivation (tables 1 and 2).…”
Section: All-age Mortalitymentioning
confidence: 99%